2011
DOI: 10.1519/jsc.0b013e31820da061
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intensity and Technical Demands of Small-Sided Games in Young Brazilian Soccer Players: Effect of Number of Players, Maturation, and Reliability

Abstract: The aims of this study were to examine in young soccer players (a) the effect of varying the number of players on exercise intensity (EI) and technical actions during small-sided games (SSGs), (b) the reliability of EI and technical actions, and (c) the influence of the players' maturation on EI and involvements with the ball (IWBs). Sixteen male soccer players (mean ± SD; age 13.5 ± 0.7 years, height 164 ± 7 cm, and weight 51.8 ± 8 kg) completed 2 bouts of 3 vs. 3 (SSG3), 4 vs. 4 (SSG4), and 5 vs. 5 (SSG5) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
52
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 17 publications
10
52
0
13
Order By: Relevance
“…This difference was significant between the SSG 3 and SSG 5 conditions. The present findings support the previous work of Rampinini et al (36) and Da Silva et al (43), which reported that a decreased number of the players on the court increased mean %HRmax (36, 43) in male participants. Further, mean HRmax in the present study approached values from competition matches (82-90% of HRmax) previously reported in the literature (3, 9, 32).…”
Section: Resultssupporting
confidence: 93%
“…This difference was significant between the SSG 3 and SSG 5 conditions. The present findings support the previous work of Rampinini et al (36) and Da Silva et al (43), which reported that a decreased number of the players on the court increased mean %HRmax (36, 43) in male participants. Further, mean HRmax in the present study approached values from competition matches (82-90% of HRmax) previously reported in the literature (3, 9, 32).…”
Section: Resultssupporting
confidence: 93%
“…The results of this study are in agreement with some similar researches 20,21 and disagreement with others that show that the types of SSG with a smaller number of players can lead to an increased number of technical skills, 16,18,19 demonstrating the need to investigate further in this direction, because there is no agreement in the literature. 37 These differences can depend by the different technical skill levels of those involved.…”
supporting
confidence: 80%
“…Thus, researchers have examined factors that may affect the intensity of SSG such as dimensions of the pitch, number of players, coach encouragement, continuous and intermittent modality, and goalkeepers' participation (da Silva et al, 2011;Hill-Haas, Dawson, Impellizzeri, & Coutts, 2011). Little and Williams (2006), and Reilly (2005) indicated that high specificity of loading, Background: Small-sided games (SSG) are spontaneous forms of specific training where exercise intensity can be manipulated mainly by modifying external factors.…”
Section: Introductionmentioning
confidence: 99%